Gaya Kognitif Field Independent Sebagai Ikhtiyar Kontrol Fokus Siswa dalam Pembelajaran - Niken Septantiningtyas; Subaida Subaida (Program Studi PGMI STAI Daruttaqwa Gresik, 2023)
The purpose of this study is to describe how the character of the field independent cognitive style of students as a control focus of their learning on aswaja learning at MI Miftahul Khoir. This study used a qualitative approach with a descriptive research type. The research data collection technique used 3 instruments, namely observation, and students' cognitive style tests through the GEFT (Group Embedded Figure Test) which included 16 items regarding control of student learning focus. The data analysis technique uses the Miles and Huberman Interactive Model with data reduction activities, data presentation, and drawing conclusions. Data validity with source and technique triangulation process. The results show that the independent field cognitive style identified by MI teacher Miftahul Khoir that out of 15 grade IV students, there are 13 students with the field independent cognitive style category and 2 students with the field dependent cognitive style category. So, it was concluded that classically as much as 86% of fourth grade students have a field independent cognitive style that is able to control student learning focus. The conditions and observations seen from students with field independent cognitive styles have characteristics in controlling the focus of their learning such as concentration of attention, verbal response, active giving statements, answering questions, and psychomotor responses. So, with this cognitive style, students are able to make it a focus control in learning and able to prove its position as a productive learning subject, not a passive-static object in learning.